Machinability of extruded and multi-directionally hot forged eco-friendly brass alloys - KAYNAK, YUSUF (My University, 2023)
Brass alloys assign a considerable portion of the industrial components\" material due to their outstanding characteristics. These materials are manufactured using hot forging or extrusion techniques, according to the application for different purposes. In this work, the metallographic and mechanical characteristics of three environmentally friendly brass alloys - CuZn40Pb2 (CW617N), CuZn38As (CW511L) and CuZn21Si3P (CW724R) - extruded and multi-directionally hot forged have been examined. By focusing on the flat bottom drilling operation, the effects of the process and type of alloying have been investigated. The examination has been accomplished on experimental data about tensile strength, impact fracture energy, cutting forces, entrance and exit burr diameters, as well as hole quality. The findings demonstrate that the most crucial criteria impacting the machining outcomes are the presence of limited Pb element and material microstructural phases, their content and mechanical characteristics, as well as the type manufacturing process.
Keywords: Metalurji ve Malzeme Mühendisliği; Mühendislik ve Teknoloji; Metallurgical and Materials Engineering; Engineering and Technology; METALURJİ VE METALURJİ MÜHENDİSLİĞİ; Malzeme Bilimi; Mühendislik, Bilişim ve Teknoloji (ENG); METALLURGY & METALLURGICAL ENGINEERING; MATERIALS SCIENCE; Engineering, Computing & Technology (ENG); Genel Malzeme Bilimi; Fizik Bilimleri; General Materials Science; Physical Sciences; Extrusion; hot forging; eco-friendly brass alloys; lead-free brass alloy; twinning; machinability; BEHAVIOR; LEAD; TEMPERATURES; Extrusion; hot forging; ecofriendly brass alloys; leadfree brass alloy; twinning; machinability